2021
DOI: 10.1021/acs.jpcc.0c11514
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Molecular Structure-Tunneling Conductance Relationships: Oligophenylene Dimethanethiol vs Oligophenylene Dithiol Molecular Junctions

Abstract: We report quantitative analysis of tunneling conductance in molecular junctions based on self-assembled monolayers (SAMs) of oligophenylene dimethanethiols (OPDMn) in which −CH2– spacers flank either side of the phenylene (n = 1), biphenylene (n = 2), and terphenylene (n = 3) aromatic cores. The current–voltage (I–V) characteristics for the OPDMn junctions with Au and Pt contacts are analyzed quantitatively with a previously validated single level model (SLM) to extract key junction metrics, namely the HOMO-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 48 publications
7
69
0
Order By: Relevance
“…By analyzing the relation of the inflection behavior in the F-N plots and transmission functions, the inflection could occur as the nearest molecular energy level was fairly approached to the resonant position within the bias window (Figure 1b). Even though the occasion of the inflection significantly is dissimilar to the conventional Simmons model, the F-N curves presented from respective calculations appear to be very analogous to those obtained from the latest experiments [37,39].…”
Section: Coherent Molecular Transport Modelsupporting
confidence: 58%
See 1 more Smart Citation
“…By analyzing the relation of the inflection behavior in the F-N plots and transmission functions, the inflection could occur as the nearest molecular energy level was fairly approached to the resonant position within the bias window (Figure 1b). Even though the occasion of the inflection significantly is dissimilar to the conventional Simmons model, the F-N curves presented from respective calculations appear to be very analogous to those obtained from the latest experiments [37,39].…”
Section: Coherent Molecular Transport Modelsupporting
confidence: 58%
“…On the contrary, the Simmons model based on a simple rectangular barrier picture seems not to tender a reasonable description for the field of molecular electronics [30][31][32][33], mostly because it is difficult to illustrate the intrinsic chemical nature of constituent molecules. Recent works by diverse research groups have consistently shown that transition voltage spectroscopy (TVS) [34][35][36][37][38][39][40][41][42], especially on the basis for the Landauer picture, can be a more accurate analytical tool, in which quantitative fits into experimental current (I)-voltage (V) curves allow conveniently extracting charge transport parameters, for instance, the alignment of the highest occupied molecular orbital (HOMO) or lowest unoccupied molecular orbital (LUMO), the tunneling transmission, and the coupling strength of molecule-electrode contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Doing so, we reproduce the individual measured I – V curves for the OPX junctions extremely well, as shown by the black traces in Figure . We believe that the very good match between the experimental and simulated I – V curves indicates that the single level model applies well for OPX-based molecular junctions, as we have shown for other molecular systems. ,, …”
Section: Resultssupporting
confidence: 60%
“…We believe that the very good match between the experimental and simulated I−V curves indicates that the single level model applies well for OPX-based molecular junctions, as we have shown for other molecular systems. [41][42][43][44][45]53,54 The average values for the transport parameters extracted from approximately 100 I−V curves for each type of OPX SAM are compiled in Table 1. Evidently, substitution of the central ring with electron donating or withdrawing groups does influence the low bias conductance G of the OPX molecular junctions, but not to a large extent.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation